Fundão Dam Disaster’s Consequences: A Characterization Study of Fishery Communities and Their Current Challenges on Rio Doce - Santos, Matheus Alves dos; Jankowsky, Mayra; Gomes, Vanielle Aparecida do Patrocinio; Mendonça, Jocemar Tomasino; Freitas, Rodrigo Randow de (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
This study characterized the profile of fishing and fishing communities, as well as the consequences that the Fundão dam break disaster in Mariana, Minas Gerais, had on artisanal fishing in the Rio Doce Basin. A total of 1,998 semi-structured questionnaires were applied in 42 municipalities along the Rio Doce, using the snowball sampling method and interviewing at least 20% of the total number of fishers in the fishing communities. The questionnaires addressed socioeconomic issues and changes in fishing activity, aiming to gather information on the impacts experienced and possible changes in the socioeconomic profile. As a result, the profile indicates the predominance of men, with an average age of 49 years, with extensive experience in fishing activities and primary education level. Small-scale fishery often occurs onshore, especially in the upper and middle reaches of the Rio Doce. Regarding the main consequences of the disaster, there is evidence of abandonment of fishing activities, especially in the upper and middle reaches of the Rio Doce, and a reduction in income. Pollution and reduction of fish stocks appear as some of the main problems, and among the expectations of local actors is the desire to return to fishing activities. Finally, it is evident that until now, fishing communities still suffer from its consequences, and there has been no recovery from fishing activities. These results are important for reparation actions to achieve their goal.